Advances in Entamoeba histolytica Biology Through Transcriptomic Analysis - Naiyer, Sarah; Bhattacharya, Alok; Bhattacharya, Sudha (Frontiers in Microbiology, 2019)
A large number of transcriptome-level studies in Entamoeba histolytica, the protozoan parasite that causes amoebiasis, have investigated gene expression patterns to help understand the pathology and biology of the organism. They have compared virulent and avirulent strains in lab culture and after tissue invasion, cells grown under different stress conditions, response to anti-amoebic drug treatments, and gene expression changes during the process of encystation. These studies have revealed interesting molecules/pathways that will help increase our mechanistic understanding of differentially expressed genes during growth perturbations and tissue invasion. Some of the important insights obtained from transcriptome studies include the observations that regulation of carbohydrate metabolism may be an important determinant for tissue invasion, while the novel up-regulated genes during encystation include phospholipase D, and meiotic genes, suggesting the possibility of meiosis during the process. Classification of genes according to expression levels showed that amongst the highly transcribed genes in cultured E. histolytica trophozoites were some virulence factors, raising the question of the role of these factors in normal parasite growth. Promoter motifs associated with differential gene expression and regulation were identified. Some of these motifs associated with high gene expression were located downstream of start codon, and were required for efficient transcription. The listing of E. histolytica genes according to transcript expression levels will help us determine the scale of post-transcriptional regulation, and the possible roles of predicted promoter motifs. The small RNA transcriptome is a valuable resource for detailed structural and functional analysis of these molecules and their regulatory roles. These studies provide new drug targets and enhance our understanding of gene regulation in E. histolytica.